Locational and Directional Dependencies of Smooth Muscle Properties in Pig Urinary Bladder - Borsdorf, Mischa; Tomalka, André; Stutzig, Norman; Morales-Orcajo, Enrique; Böl, Markus; Siebert, Tobias (Frontiers in Physiology, 2019)
The urinary bladder is a distensible hollow muscular organ, which allows huge changes in size during absorption, storage and micturition. Pathological alterations of biomechanical properties can lead to bladder dysfunction and loss in quality of life. To understand and treat bladder diseases, the mechanisms of the healthy urinary bladder need to be determined. Thus, a series of studies focused on the detrusor muscle, a layer of urinary bladder made of smooth muscle fibers arranged in longitudinal and circumferential orientation. However, little is known about whether its active muscle properties differ depending on location and direction. This study aimed to investigate the porcine bladder for heterogeneous (six different locations) and anisotropic (longitudinal vs. circumferential) contractile properties including the force-length-(FLR) and force-velocity-relationship (FVR). Therefore, smooth muscle tissue strips with longitudinal and circumferential direction have been prepared from different bladder locations (apex dorsal, apex ventral, body dorsal, body ventral, trigone dorsal, trigone ventral). FLR and FVR have been determined by a series of isometric and isotonic contractions. Additionally, histological analyses were conducted to determine smooth muscle content and fiber orientation. Mechanical and histological examinations were carried out on 94 and 36 samples, respectively. The results showed that maximum active stress (pact) of the bladder strips was higher in the longitudinal compared to the circumferential direction. This is in line with our histological investigation showing a higher smooth muscle content in the bladder strips in the longitudinal direction. However, normalization of maximum strip force by the cross-sectional area (CSA) of smooth muscle fibers yielded similar smooth muscle maximum stresses (165.4 ± 29.6 kPa), independent of strip direction. Active muscle properties (FLR, FVR) showed no locational differences. The trigone exhibited higher passive stress (ppass) than the body. Moreover, the bladder exhibited greater ppass in the longitudinal than circumferential direction which might be attributed to its microstructure (more longitudinal arrangement of muscle fibers). This study provides a valuable dataset for the development of constitutive computational models of the healthy urinary bladder. These models are relevant from a medical standpoint, as they contribute to the basic understanding of the function of the bladder in health and disease.